The Dynamic Tapestry of Transnationalism: Examining South Asian Diasporic Identities in Sonya Lalli’s Grown Up Pose - Tariq, Misbah; Rukh, Harmain; Javed, Sobia (Journal of Development and Social Sciences, 2024)
This study delves into the depiction of transnationalism in Sonya Lalli’s Grown Up Pose, emphasizing the intricate and pluralistic identities of South Asian diasporic characters as they traverse the complexities of a hyper-connected global milieu. Drawing upon Steven Vertovec’s transnationalism theory and employing rigorous textual analysis, the study examines the fluidity of identity and the formation of multifaceted social networks within the diaspora, highlighting their participation in cross-cultural dialogues and negotiation of liminal spaces. By meticulously deconstructing these elements, this study advocates for a more expansive and nuanced interpretation of diasporic experiences, one that transcends the confines of historical trauma to foreground the proactive construction of interconnected transnational networks. The findings underscore the potential of transnational spaces to foster inclusivity, equity, and the reconfiguration of cultural narratives, thereby advancing the discourse on the South Asian diaspora in the digital era.